Refinement of immunizing antigens to produce functional blocking antibodies against the AniA nitrite reductase of Neisseria gonorrhoeae. - Lucy K Shewell; Freda E-C Jen; Michael P Jennings (PLoS ONE)
The emergence of multi-drug resistant Neisseria gonorrhoeae has generated an urgent need for novel therapies or a vaccine to prevent gonococcal disease. In this study we investigate the potential of targeting the surface exposed nitrite reductase, AniA, to block activity by producing functional blocking antibodies. AniA activity is essential for anaerobic growth and biofilm formation of N. gonorrhoeae and functional blocking antibodies may prevent colonisation and disease. Seven peptides covering regions adjacent to the active site were designed based on the AniA structure. Six of the seven peptide conjugates generated immune responses. Peptide 7, GALGQLKVEGAEN, was able to elicit antibodies capable of blocking AniA activity. Antiserum raised against the peptide 7 conjugate detected AniA in 20 N. gonorrhoeae clinical isolates. Recombinant AniA protein antigens were also assessed in this study and generated high-titre, functional blocking antibody responses. Peptide 7 conjugates or truncated recombinant AniA antigens have potential for inclusion in a vaccine against N. gonorrhoeae.